PENGEMBANGAN SUMBER BELAJAR DIGITAL BERBASIS E-BOOK BEBASO PELEMBANG UNTUK SISWA KELAS V DI SEKOLAH DASAR - Carisa Intan Choirunissa; Muhamad Idris; David Budi Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a digital learning resource in the form of an E-Book titled “Kamus Praktis Bebaso Palembang” for fifth-grade students at SD Negeri 07 Palembang. The background of the research lies in the lack of digital-based learning resources that integrate local cultural content, particularly the use of Bebaso Palembang (Palembang refined language), which is gradually fading among students. This study employed a Research and Development (R&D) approach using the 4D model consisting of Define, Design, Develop, and Disseminate, but only implemented the first three stages: Define, Design, and Develop. The development process began with needs analysis, learner analysis, task analysis, concept analysis, and instructional objectives formulation. The design stage involved media selection, content structuring, and initial product development. The development stage included validation by subject matter experts, media experts, and language experts, as well as practicality tests through student response questionnaires and interviews. The validation results show that the E-Book is “very valid” with an average score of 88.76%. Practicality tests show a percentage of 83.38%, indicating that the E-Book is